Rural Development Research Trends: Bibliometric Analysis Using Publish or Perish and Vosviewer - Komang Ariyanto (Athena: Journal of Social, Culture and Society, 2023)
This article aims to revisit the study of rural development, agricultural development, and rural livelihoods by highlighting publications in Google Scholar and Semantic Scholar from 1980 to 2023. The study utilized Google Scholar's and Semantic Scholar's 43-year citation database to compile articles. The keywords used in this study were "Rural Development," "Agricultural Development," and "Rural Livelihoods," with English document filters applied through the Publish or Perish software. Descriptive statistical methods were used to present graphs, diagrams, tables, and literature reviews. Subsequently, a bibliometric analysis was performed on the data using the VOSviewer software. In this study, visualization of citations and keywords was conducted. The study reveals significant research trends in rural development, agricultural development, and rural livelihoods over the past 43 years. Based on the visualization of a large cluster network map containing concepts related to rural development, agricultural development, and rural livelihoods, various advancements in concept development emerged. Studies on the mathematical modeling of rural development, agricultural development, and rural livelihoods remain separate. No study has integrated the topic of agricultural development and rural livelihoods within the context of agricultural development. The researcher further employs bibliometric analysis to identify relevant keywords related to the topics of study: rural development, agricultural development, and rural livelihoods. Thus, the researchers suggest further study on the rationalization of farmers in dryland areas to realize food security for local communities' livelihoods. Additionally, studying agricultural development programs on dryland areas is necessary, integrating the perspective of sustainable livelihoods to support and realize sustainable rural development